Foreign Body in the Scalp: A Rare Cause of Recurrent Headache - Işıkay, Sedat (Springer, 2016)
To the Editor: A 9-y-old boy was admitted to the hospital with a complaint of continuous headache, starting from left part of his head and radiating through all parts. He was localizing the beginning and maximal point of the headache with his hand. He denied having any head trauma and his general physical examination was normal.
Keywords: Headache